2009
DOI: 10.1080/03069880902957031
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic applications of the mobile phone

Abstract: As the availability of new communication technologies increases, mental health professionals have incorporated these innovations into their practice and research. Up to now several studies have presented promising results in using the power and convenience of the Internet for clinical care. While multiple contributions focus on the potential and the advantages of therapies delivered through the Internet, mental health practitioners may take into account new technological opportunities to improve their practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 34 publications
3
72
0
5
Order By: Relevance
“…Additionally, although there is some evidence of comparable compliance rates between paper-and-pencil and handheld electronic device EMA methods (Green, Rafaeli, Bolger, Shrout, & Reis, 2006), other studies have found evidence that the use of experimenter-provided mobile phones in completing surveys shows a higher level of participant compliance than paper-and-pencil EMA methodologies (Preziosa, Grassi, Gaggioli, & Riva, 2009). …”
Section: Handheld Devicesmentioning
confidence: 99%
“…Additionally, although there is some evidence of comparable compliance rates between paper-and-pencil and handheld electronic device EMA methods (Green, Rafaeli, Bolger, Shrout, & Reis, 2006), other studies have found evidence that the use of experimenter-provided mobile phones in completing surveys shows a higher level of participant compliance than paper-and-pencil EMA methodologies (Preziosa, Grassi, Gaggioli, & Riva, 2009). …”
Section: Handheld Devicesmentioning
confidence: 99%
“…En los últimos años, se han desarrollado apps para la salud mental que han demostrado un buen potencial para el manejo del estrés y la ansiedad (Preziosa, Grassi, Gaggioli y Riva, 2009;Repetto et al, 2013;Villani y Riva, 2012;Villani et al, 2013). En este sentido podemos citar algún ejemplo de apps disponibles para la atención de los trastornos emocionales en el periodo prenatal.…”
Section: Herramientas De Salud Prenatal Alternativas Basadas En Las Tunclassified
“…Some of these areas include the use of mobile phones for managing exam stress (Preziosa, Grassi, Gaggioli, & Riva, 2009), a mobile-based stress-management program for employees (Heber et al, 2013), and a mobile-based program for reducing stress during commuting trips ). According to Cleland, Caldow, and Ryan (2007), among the many advantages of using a mobile approach to reduce stress could include: 1) an acquisition of coping skills in a more autonomous way, 2) allowing for a more ubiquitous and effective support in facing daily stressful situations, 3) an enhancement of people's compliance, and 4) the possibility of living graded exposure experiences in real-world settings.…”
Section: Mhealth Technologiesmentioning
confidence: 99%
“…In particular, mobile phones are gaining particular importance in health care services (Free et al, 2010;Kumar et al, 2013), as there appears to be a large increase in the use of mobile phones for a variety of therapeutic applications (Preziosa, Grassi, Gaggioli, & Riva, 2009). According to Cleland, Caldow, and Ryan (2007), among the many advantages of using a mobile approach to reduce stress could include both an incremental acquisition of coping skills in a more autonomous way, as well as allowing for a more ubiquitous and effective support in facing daily stressful situations.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation